Panel data estimates of the production function and product and labor market imperfections - Sabien Dobbelaere; Jacques Mairesse (European Central Bank (ECB), 2007)
Embedding the efficient bargaining model into the Hall (1988) approach for estimating price-cost margins shows that both imperfections in the product and labor markets generate a wedge between factor elasticities in the production function and their corresponding shares in revenue. This article investigates these two sources of discrepancies both at the industry and the firm level using an unbalanced panel of 10646 French firms in 38 manufacturing industries over the period 1978-2001. By estimating standard production functions, we are able to derive estimates of average price-cost mark-up and rent sharing parameters. Our industry-level results indicate that industry differences in these parameters are quite sizeable. To determine the degree of true firm-level heterogeneity, we adopt the Swamy (1970) methodology. The Swamy robust estimates of true dispersion show sizeable within-industry firm heterogeneity. Firm size, capital intensity, distance to the industry technology frontier and investing in R&D seem to account for part of this heterogeneity.
Keywords: C33; D21; J51; L13; 330; panel data; price-cost mark-ups; production function; Rent sharing; Produktionsfunktion; Faktorintensität; Substitutionselastizität; Matching; Faktorpreis; Produktivität; Industrie; Frankreich